Ethnic mythology as symbolic capital for nation branding: a heuristic assignment for students - Kurbacheva, Olga V. (University Pedagogical Journal, 2026)
A version of an open-ended heuristic assignment on ethnic mythology and its contemporary application in the context of national branding is presented. Developed for philosophy students majoring in «Fundamentals of modern anthropology », the assignment aims to illustrate the feasibility and practical feasibility of studying ethnomythology as part of the social and humanities curriculum for higher education students. It emphasises that ethnic mythology is not outdated archival knowledge, but a unique symbolic asset that can be applied to strengthening ethnocultural identity and constructing a national image and brand at the current stage of national development. The lesson focuses on developing systemic and critical thinking, as well as fostering civic awareness and a value-based approach to one’s history.
Keywords: ethnomyth; self-awareness; remythologisation; ethno-renaissance; nation branding